HOUT-03. SCREENING FOR MOOD DISTURBANCE IN LONG-TERM CENTRAL NERVOUS SYSTEM (CNS) TUMOR SURVIVORS USING PATIENT REPORTED OUTCOMES MEASUREMENT INFORMATION SYSTEM (PROMIS): A NEURO-ONCOLOGY BRANCH NATURAL HISTORY STUDY (NOB-NHS) REPORT. (5th November 2018) - Ruiz, María Fletcher; Vera, Elizabeth; Acquaye, Alvina; Boris, Lisa; Brown, Miranda; Crandon, Sonja; Garren, Nancy; Ji, Ming; Levine, Jason; Reyes, Jennifer; Siegel, Christine; Wu, Jing; et al.
Abstract: BACKGROUND: Survivorship is an important area of cancer care and research. There are limited studies exploring the experience of long term survivors of CNS tumors. A recent review of quality of life in adults with CNS tumors underscored the need for studies exploring patient outcomes, including mood disturbance. This report explores mood disturbance in CNS tumor patients living greater than 5 years from diagnosis. METHODS: Patients enrolled on the NOB-NHS were included. PROMIS depression/anxiety measures were completed at study entry. T-scores >60 were considered significant. Independent sample t-tests, chi-square and Fishers Exact tests were used to identify associations with mood disturbance. Significance level was set at 0.05. RESULTS: 132 patients, primarily white (84%), males (58%), with median age 49 (22–81), were included with 59% having low grade tumors; oligodendroglioma (19%) was the most common diagnosis, 30% underwent gross total resection, 33% had had a recurrence and 27% had a poor KPS (80). Five percent were on corticosteroids and 20% on psychotropic medications. Overall, 14% and 18% reported significant depression and anxiety respectively, with 10% reporting both. More non-white [29% vs 11%; X2 (1) = 4.4, p<0.04] reported significant depressive symptoms, as did those with poor KPS [25% vs. 10%; X2 (1) = 4.2, p<0.04] and those on psychotropic medications [27% vs 11%; X2 (1) = 4.5, p<0.04]. Anxiety was only associated with the use of psychotropic medications [38% vs. 13%; X2 (1) = 9.3, p<0.01]. CONCLUSION: Symptoms of depression and anxiety occurred in 20% of long-term brain tumor survivors on screening. Depressive symptoms were associated with race, lower KPS, and use of psychotropic medications. Additionally, use of psychotropic medications was associated with anxiety. Assessment of depression and anxiety as part of survivorship care is warranted. Future studies exploring phenotypes at risk and targeted interventions are needed to mitigate these symptoms.